1969
DOI: 10.1039/c29690000192
|View full text |Cite
|
Sign up to set email alerts
|

A σ-bonded cobalt allene

Abstract: Sumwzary A o-bonded cobalt allene has been prepared by the reaction of the bis (dimethylg1yoximato)pyridinecobalt (I) anion with prop-2-ynyl bromide. Although another o-bonded allenyl-metal compound had been prepared previously, it is incorrectly described as a uprop-2-ynyl compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 0 publications
6
69
0
1
Order By: Relevance
“…D145E also generated a leftward shift with a ⌬pCa 50 of ϩ0.25. At the 50% ratio only A8V showed a corresponding decrease in pCa 50 compared with the amount of mutant protein present (Fig. 1B).…”
Section: Actomyosin Atpase Pca Curves Using Reconstituted Troponin Comentioning
confidence: 99%
See 1 more Smart Citation
“…D145E also generated a leftward shift with a ⌬pCa 50 of ϩ0.25. At the 50% ratio only A8V showed a corresponding decrease in pCa 50 compared with the amount of mutant protein present (Fig. 1B).…”
Section: Actomyosin Atpase Pca Curves Using Reconstituted Troponin Comentioning
confidence: 99%
“…The data were fitted to a version of the Hill equation that accounted for the spectral changes that occur at a low Ca 2ϩ concentration and plotted using SigmaPlot 10.0. The apparent Ca 2ϩ affinities are reported as pCa 50 values ϮS.E.…”
Section: Determination Of Apparent Ca 2؉ Affinities By Fluorescencementioning
confidence: 99%
“…Several groups (24,(41)(42)(43)(44) have demonstrated that the binding of Ca 2ϩ to the low affinity site initiates muscle contraction. Removal of Ca 2ϩ from the Ca 2ϩ -specific sites in skeletal TnC has also been linked to structural changes in TnC (41,45,46). The effect of cTnT and/or TnI isoforms on the rate of Ca 2ϩ removal from either the high or low affinity Ca 2ϩ -binding sites on cTnC has not been examined previously.…”
Section: ϫ015) Than Intact Fibers Similar To What Has Been Reported mentioning
confidence: 99%
“…Previous studies in this laboratory (49) have shown that of the total Ca 2ϩ -induced ellipticity in intact TnC, ϳ27% could be assigned to N domain and ϳ73% to C domain. Rather similar large contributions by C domain were reported by Johnson and Potter (50). To eliminate the large background of -activated tensions (pCa 6.2-4.4) were measured in native rabbit psoas fibers, followed by extraction of endogenous TnC and reconstitution with sTnC F29W or chicken muscle TnC, as described under "Materials and Methods."…”
Section: Tension Measurements-mentioning
confidence: 99%